2014
DOI: 10.1016/j.jobcr.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral calcifying epithelial odontogenic tumor – Case report

Abstract: The calcifying epithelial odontogenic tumor (CEOT), Pindborg tumor is a benign, slow growing, but locally invasive neoplasm. It is known to have a common intraosseous variant and a very rare extraosseous variant. We report an unusual case of an extraosseous variant of CEOT of unusual large size and maxillary anterior location, the treatment was planned considering the clinical, radiological and histological features. Though peripheral types are less aggressive and had no recurrence, in our case regular follow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Only one case described by Shetty et al (2014) showed an atypical presentation of peripheral CEOT with great dimensions and calcifications and was treated through maxillectomy [4]. Despite these characteristics in the present case as well as elsewhere, there are a few cases with evidence of relapse [1, 4, 8]. …”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Only one case described by Shetty et al (2014) showed an atypical presentation of peripheral CEOT with great dimensions and calcifications and was treated through maxillectomy [4]. Despite these characteristics in the present case as well as elsewhere, there are a few cases with evidence of relapse [1, 4, 8]. …”
Section: Discussionmentioning
confidence: 63%
“…In a recent literature review, Shetty et al (2014) reported that peripheral CEOT is more common among females in the third and fourth decade of life (mean age of 37.33 years), usually affecting the anterior region of the maxilla [4]. Although the majority of the lesions are unilateral, studies have reported cases of bilateral lesions and tumours in maxilla and mandible simultaneously [2, 8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations